Interrelationships of psychoemotional reactions in women after perinatal loss: correlation analysis - But Тетяна; Mukharovska Інна (Psychosomatic Medicine and General Practice, 2026)
Background. Perinatal loss is associated with a wide range of psychoemotional and somatic reactions that often exhibit a comorbid pattern. However, the structural relationships between grief, posttraumatic stress, affective distress, somatic symptoms, avoidance, and negative cognitions remain insufficiently explored. Understanding these associations is important for substantiating a comprehensive approach to psychological support for women after perinatal loss. Methods. A cross-sectional study was conducted (n=67 women; August 2023 – October 2025) using an online survey with snowball sampling. Nine validated psychometric instruments were applied: TGI-SR+, PGS, PCL-5, PHQ-4, SSS-8, DAAPGQ, GCQ, CSI-32, and SCES+. Normality was assessed using the Shapiro–Wilk test; due to mixed distribution patterns, Spearman’s rank correlation was used for all variable pairs. Analyses were performed using Python and EZR v1.54; the level of significance was set at p<0.05. Results. A consistent pattern of associations between indicators of psychoemotional distress was identified. Measures of grief intensity (TGI-SR+, PGS), posttraumatic stress (PCL-5), anxious-depressive distress (PHQ-4), avoidance (DAAPGQ), negative cognitions (GCQ), and somatic distress (SSS-8) demonstrated moderate to strong positive correlations (ρ=0.47–0.86, all p<0.001). The strongest association was observed between negative cognitions and perinatal grief intensity (GCQ and PGS; ρ=0.861). Coping efficacy (SCES+) showed stable negative correlations with all symptomatic indicators (ρ=−0.46–−0.67, all p<0.001), whereas relationship satisfaction (CSI-32) was positively associated with SCES+ (ρ=0.25, p<0.05) and negatively with PCL-5 (ρ=−0.29, p<0.05). Discussion. The findings indicate a high degree of interrelatedness among psychoemotional responses following perinatal loss and are consistent with transdiagnostic approaches to understanding psychological distress. Coping efficacy appears to function as a potential protective factor, while relationship satisfaction represents an additional relational resource. Conclusions. Psychoemotional responses after perinatal loss are characterized by strong interconnections between grief, traumatic stress, affective, and somatic distress. Coping efficacy emerges as a key protective factor. The findings support the relevance of a comprehensive approach to psychological support following perinatal loss. Keywords: perinatal loss; grief; posttraumatic stress disorder; depression; anxiety; somatic distress; coping; correlation analysis; psychological adaptation. УДК 159.9:616.89:618.39